Enhancing Agricultural Extension Programs: A Practical Guide to Designing and Implementing Randomized Controlled Trials - Amin ABU-ALSOUD; Ameur Mehrez; Houcine Bichni (مجلة جامعة النجاح للأبحاث العلوم الطبيعية)
Evidence-based practices in agricultural extension programs must be guided by precise evaluation strategies and reliable data. Methods like randomized controlled trials (RCTs) are vital for assessing specific program interventions. However, not all studies use experimental designs, and their quality varies, as noted in a 2010 World Bank study. RCTs, known for providing robust impact assessments, involve complex steps and are applied in various fields. This guide focuses specifically on RCTs used for agricultural extensions; a topic covered less often than clinical trials. More precisely, this guide provides (1) definitions and key steps for RCTs, (2) a simplified RCTs study design methodology, (3) an exploration of challenges and mitigation, and (4) a summary of relevant RCTs studies in extensions. This guide is formulated to enhance the present understanding of RCTs and elaborate on the ways to use them in their application in agricultural research. Furthermore, the goal here is to make sure that our policies and methods are presented with solid evidence. This approach is meant to encourage the implementation of agricultural practices that are not only more effective but also sustainable.